Longitudinal analysis of 2293 NSCLC patients: A comprehensive study from the TYROL registry. Issue 2 (February 2015) - Kocher, Florian; Hilbe, Wolfgang; Seeber, Andreas; Pircher, Andreas; Schmid, Thomas; Greil, Richard; Auberger, Jutta; Nevinny-Stickel, Meinhard; Sterlacci, William; Tzankov, Alexandar; Jamnig, Herbert; Kohler, Karin; et al.
Highlights Cumulative analysis of a large NSCLC cohort. Detailed information on symptoms and comorbidities at diagnosis. Correlation of baseline characteristics and outcome. Step-by-step analysis of response and outcome in different therapeutic settings.